The Humanitarian Tragedy of "Wadas and Rempang Island" Forms of Neo-Colonialism and New-Style Neo-Capitalism and the Collapse of Law in Indonesia - Sugeng Dwiono; Slamet Haryadi; Iskandar Iskandar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The clash on September 7, 2023, between Rempang residents and security forces (POLRI, TNI), which ended with the arrest of 43 residents, mirrors the conflict that occurred between the residents of Wadas Village, Bener Subdistrict, Purworejo Regency, Central Java, and the Central Java Regional Government on February 8, 2022. The violence perpetrated by security forces against the residents of Rempang Island occurred when the company, escorted by security, unilaterally staked out Malay customary land in 16 traditional villages on Rempang and Galang Islands in the Riau Archipelago, covering an area of 17,600 hectares. This included 10,028 hectares of protected forest, or about 45.84% of the total land area, which they had occupied since 1834. According to the head of Batam Concessionaires (BP), Muhammad Rudi, the Eco City development plan has been underway since 2004. At that time, PT. Makmur Elok Graha and Xinyi Glass Holding Ltd. (July 2023), the exclusive rights holders, became the private entities partnered with the government (September 12, 2023), receiving an 80-year concession from the government. The government's actions of land seizure and violence demonstrate a form of power arrogance that tends toward abuse of power, under the pretext of protecting a 381 trillion investment, while ignoring the rights of citizens as stipulated in the 1945 Constitution and the Basic Agrarian Law. The government's actions represent forms of Neo-Colonialism and Neo-Capitalism occurring during the Jokowi administration. This situation underscores that the law is no longer equal; the law has collapsed, becoming merely a symbol that only favors power.